Hygrothermal effects on damping behavior of metal/glass fiber/epoxy hybrid composites - Botelho, E. C.; Pardini, L. C.; Rezende, M. C. (Elsevier B.V., 2005)
Continuous fiber/metal laminates (FML) offer significant improvements over current available materials for aircraft structures due to their excellent fatigue endurance and low density. Glass fibers/epoxy laminae and aluminum foil (Glare) are commonly used to obtain these hybrid composites. The environmental factors can limit the applications of composites by deteriorating the mechanical properties during service. Usually, epoxy resins absorb moisture when exposed to humid environments and metals are prone to surface corrosion. Therefore, the combination of the two materials in Glare (polymeric composite and metal). can lead to differences that often turn out to be beneficial in terms of mechanical properties and resistance to environmental influences. In this work. The viscoelastic properties. such as storage modulus (E') and loss modulus (E'), were obtained for glass fiber/epoxy composite, aluminum 2024-T3 alloy and for a glass fiber/epoxy/aluminum laminate (Glare). It was found that the glass fiber/epoxy (G/E) composites decrease the E' modulus during hygrothermal conditioning up to saturation point (6 weeks). However, for Glare laminates the E' modulus remains unchanged (49GPa) during the cycle of hygrothermal conditioning. The outer aluminum sheets in the Glare laminate shield the G/E composite laminae from moisture absorption. which in turn prevent, in a certain extent, the material from hygrothermal degradation effects. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: metal/glass fiber composites; damping; behavior; elastic properties